Exploring the potential of doped zero-dimensional cages for proton transfer in fuel cells: a computational study - Mane, Manoj V.; Venkatnathan, Arun; Ghatak, Kamalika; Vanka, Kumar (Journal of Physical Chemistry B, 2012)
Calculations with density functional theory (DFT) and MP2 have been done to investigate the potential of recently synthesized durable zero-dimensional (OD) nitrogen-based cage structures to perform as efficient proton-exchange membranes (PEMs) in fuel cells. Our calculations suggest that the hydrogenated 0-D cages, in combination with hydrogen-bonding 1,2,3- and 1,2,4-triazole molecules, would perform as highly efficient PEMs. The results are important in the context of the need for efficient PEMs for fuel cells, especially at higher temperatures (greater than 120 degrees C) where conventional water-based PEMs such as Nafion have been found to be ineffective.